2022
DOI: 10.48550/arxiv.2207.02248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telescope Concepts in Gamma-Ray Astronomy

Abstract: This chapter outlines the general principles for the detection and characterisation of high-energy γ-ray photons in the energy range from MeV to GeV. Applications of these fundamental photon-matter interaction processes to the construction of instruments for γ-ray astronomy are described, including a short review of past and present realisations of telescopes. The constraints encountered in operating telescopes on high-altitude balloon and satellite platforms are described in the context of the strong instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 89 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…1.1 and 1.2. Measurements in the MeV regime suffer from a scarcity of photons from astrophysical sources, carrying a million times more energy in one quantum than optical photons, for example, large instrumental background (Diehl et al, 2018;Siegert et al, 2019b), and apertures which align more with particle detectors in space rather than telescopes (Siegert et al, 2022d). Images are therefore often either 'reconstructed', i.e.…”
Section: A Puzzling Picturementioning
confidence: 99%
See 2 more Smart Citations
“…1.1 and 1.2. Measurements in the MeV regime suffer from a scarcity of photons from astrophysical sources, carrying a million times more energy in one quantum than optical photons, for example, large instrumental background (Diehl et al, 2018;Siegert et al, 2019b), and apertures which align more with particle detectors in space rather than telescopes (Siegert et al, 2022d). Images are therefore often either 'reconstructed', i.e.…”
Section: A Puzzling Picturementioning
confidence: 99%
“…It is not excluded that the disk may actually not be the Galactic disk, but rather halo emission or even foreground. In the latter two cases, inferences with SPI would suffer from its coded aperture mask design, being almost incapable of measuring isotropic emission or shallow gradients (Caroli et al, 1987;Siegert et al, 2022d). In addition, Siegert et al (2019b) showed that there is hardly a trend of Doppler-shifts in the 511 keV line along Galactic longitudes, which would verify a rotation curve and the extended emission beyond the bulge as the Galactic disk.…”
Section: Introduction 1what Do We See?mentioning
confidence: 99%
See 1 more Smart Citation